2012
DOI: 10.1139/b2012-097
|View full text |Cite
|
Sign up to set email alerts
|

Monophyly of some North American species ofRamalinaand inferred polyketide synthase gene function

Abstract: Ramalina thrausta (Ach.) Nyl., Ramalina roesleri (Hochst. Ex Schaerer) Hue, and Ramalina dilacerata (Hoffm.) Hoffm. are three common North American species that have not been placed in a phylogeny and are sympatric in their distribution leading to uncertainty about monophyly. Species characters include secondary metabolites (polyketides) in Ramalina that may be both hereditary and influenced by environmental conditions, but little is known about the function of polyketide synthase (PKS) genes. The main goal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The ITS barcoding locus has been recommended for Fungi (Schoch et al 2012) and has been successfully employed in several studies of species delimitation and population genetics in the genus Ramalina (Groner & LaGreca 1997; LaGreca 1999; Stocker-Wörgötter et al 2004; Ohmura et al 2008; Sérusiaux et al 2010; Francisco de Oliveira et al 2012; Timsina et al 2012; Del Campo et al 2013; Hayward et al 2014). Thus, while some workers such as Kashiwadani & Moon (2002) accept R. pollinaria in a broad sense, phylogenetic studies on North American representatives using ITS (Timsina et al 2012) suggest that this is a polyphyletic entity. Ohmura et al (2008), after revision of the three phenotypically similar species R. pollinaria , R. yasudae and R. sekika , confirmed the status of the last two taxa as separate from R. pollinaria in East Asia, and they are actually not closely related to R. pollinaria .…”
Section: Introductionmentioning
confidence: 99%
“…The ITS barcoding locus has been recommended for Fungi (Schoch et al 2012) and has been successfully employed in several studies of species delimitation and population genetics in the genus Ramalina (Groner & LaGreca 1997; LaGreca 1999; Stocker-Wörgötter et al 2004; Ohmura et al 2008; Sérusiaux et al 2010; Francisco de Oliveira et al 2012; Timsina et al 2012; Del Campo et al 2013; Hayward et al 2014). Thus, while some workers such as Kashiwadani & Moon (2002) accept R. pollinaria in a broad sense, phylogenetic studies on North American representatives using ITS (Timsina et al 2012) suggest that this is a polyphyletic entity. Ohmura et al (2008), after revision of the three phenotypically similar species R. pollinaria , R. yasudae and R. sekika , confirmed the status of the last two taxa as separate from R. pollinaria in East Asia, and they are actually not closely related to R. pollinaria .…”
Section: Introductionmentioning
confidence: 99%
“…2004; Timsina et al . 2012; Pérez-Vargas & Pérez-Ortega 2014; Gasparyan et al . 2017) have all indicated that R .…”
Section: Discussionmentioning
confidence: 99%
“…(2004) and Timsina et al . (2012) that Ramalina species containing medullary products are derived. By contrast, all Ramalina species that lack these medullary products are found in clades K, L, M and N. Furthermore, interestingly, compared to all but one of the species ( R .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations